Dietary Patterns and Gestational Weight Gain and Postpartum Weight Loss: A NESR Systematic Review. (7th June 2021) - Raghavan, Ramkripa; Donovan, Sharon M; Dewey, Kathryn; Novotny, Rachel; Stang, Jamie; Taveras, Elsie; Kleinman, Ronald; Nevins, Julie; Scinto-Madonich, Sara; Kim, Julia; Butera, Gisela; Terry, Nancy; et al.
Abstract: Objectives: To inform the 2020–2025 Dietary Guidelines for Americans, USDA and HHS identified important public health questions to be examined by the 2020 Dietary Guidelines Advisory Committee. The Committee conducted 2 systematic reviews with support from USDA's Nutrition Evidence Systematic Review (NESR) team to answer the following questions: What is the relationship between dietary patterns (DP) consumed during 1) pregnancy and gestational weight gain (GWG)?, and 2) lactation and postpartum weight loss (PPWL)? Methods: The Committee developed protocols that described how they would use NESR's systematic review methodology to examine the systematic review questions. NESR conducted a literature search and dual-screened the results using pre-defined inclusion and exclusion criteria to identify articles published between Jan 2000 and Nov 2019. NESR extracted data and assessed risk of bias of included studies. The Committee synthesized the evidence, developed conclusion statements, and graded the strength of the evidence underlying the conclusion statements. Results: Twenty-six articles were included in the GWG review and 1 article in the PPWL review. The GWG review included 5 RCTs and 21 prospective cohort studies. Two RCTs showed that a "beneficial" DP was associated with lower GWG. Thirteen of the 20 observational studies showed an association between DP and GWG. Although the DPs examined were characterized by different combinations of foods and beverages, the patterns consistently associated with lower GWG were higher in vegetables, fruits, nuts, legumes, and fish and lower in added sugars and red and processed meats. The PPWL review included only one RCT, which was limited by high attrition, issues with implementing the intervention, and lack of blinding. Conclusions: Limited evidence suggests that certain DPs during pregnancy are associated with a lower risk of excessive GWG. These patterns are higher in vegetables, fruits, nuts, legumes, and fish, and lower in added sugar, and red and processed meat (Grade: Limited). Insufficient evidence is available to determine the relationship between DPs during lactation and PPWL (Grade: Grade Not Assignable). Funding Sources: USDA, Food and Nutrition Service, Center for Nutrition Policy and Promotion.